Ideologi Pendidikan Pondok Pesantren Al-Islam Tenggulun Solokuro Lamongan - Taufik Nugroho (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2019)
This research is motivated by the fact that there are some pesantren alumni and their caregivers involved in acts of radicalism. Based on the facts above, the researcher is interested in conducting research on the ideological aspects. Many people believe that a person's actions are guided and validated by the ideology he believes in. For this reason the question arises, ‘what is the ideology of education in the pesantren al-Islam, Tenggulun, Solokuro?" To answer this question, the researcher investigates information in the pesantren by participating; stayed in the location for some time, following a number of activities carried out by the pesantren. Information to be sought is: ideology of pesantren education, books or study materials for pesantren, curriculum implementation in learning in pesantren. The results of the investigation are as follows: The ideology of al-Islam Islamic Boarding School education is theo-centric humanism. The implementation of the educational ideology is carried out in three stages, first tarbiyah, second, hijrah and third jihad.